Technology, Organization, and Structure—A Morphogenetic Approach - Mutch, Alistair (Organization Science, 2010)
This article relates Archer's morphogenetic approach, derived from the philosophical tradition of critical realism, to the use of information and communication technology in organizations. Three gains are seen to accrue from this approach: greater clarity about the material properties of technology, links to broader structural conditions arising from the conceptualization of the relationship between agency and structure, and the potential to explore the importance of reflexivity in contemporary organizations, especially in conditions of the widespread use of information and communication technology. The importance of disaggregating the artifacts of this technology into levels and features is stressed to enable analysis to explore the specific impacts of particular combinations. This is developed through a discussion of data warehousing in connection with the attention being given to the importance of analytics in organizational strategies. Key features are in wider aspects of the cultural and structural context, demonstrating the fruitfulness of a morphogenetic approach.